Infant Weight Gain and the Effects of Massage Performed with Gentle Strokes or Tactile Stimulation of the Skin Surface (Infant Massage) - Astin Nur Hanifah; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
ABSTRACT Infant growth is an important indicators in assessing child health and development . One of the most commonly used parameters for evaluating infant growth is weight gain. Various factors May influence infant weight gain, including stimulation through infant Infant massage​ massage is a gentle tactile stimulation applied to the baby's skin to improve comfort , blood circulation , sleep quality , and growth . This study aimed to determine the effect of infant massage on infant weight gain. This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design . The sample consisted of 30 infants aged 1–6 months selected through purposive sampling. The intervention involved infant massage conducted three times per week for four weeks . Data were analyzed using the Paired Sample t- Test . The results showed that the mean infant weight increased from 5.82 ± 0.84 kg before the intervention to 6.54 ± 0.88 kg after the intervention . Statistical analysis revealed a p- value of 0.000 (p < 0.05), indicating a significant effect of infant massage on infant weight gain. Keywords : Infant Massage , Infant Weight Gain, Tactile Stimulation , Infant Growth , Child Health